CONCEPTUAL APPROACH TO IDENTIFICATION OF THE PROTECTION OF THE ORGANIZATION OF MANAGEMENT ACCOUNT FOR BUILDING ENTERPRISES - Pylypiv N.І.; Motyl, V.M. (The actual problems of regional economy development, 2017)
The article examines the issue of determining the necessary provision of the process of organizing management accounting in construction companies in order to form a conceptual approach to its identification, taking into account changes in the modern information environment. Established that the technological process of accounting procedures should be ensured: organizationally, informational, technically, methodically, socially, ergonomically and resourcefully. According to the results of the research, the classification of resource support for the management accounting process has been developed, which determines the importance of using such resources in order to successfully implement the strategy of enterprise development in the modern information environment.